2019
DOI: 10.1021/acs.iecr.9b01891
|View full text |Cite
|
Sign up to set email alerts
|

Role of Characterization in the Accuracy of PC-SAFT Equation of State Modeling of Asphaltenes Phase Behavior

Abstract: The ability to capture asphaltene precipitation conditions is key to minimize costs associated with production caused by asphaltene depositing and blocking wellbores and pipelines. In this work, modeling of asphaltene precipitation of crude oils is performed using the perturbed chain form of the statistical associating fluid theory (PC-SAFT) equation of state (EoS). The characterization of choice is crucial to the accuracy obtained from any equation of state. Therefore, an alternative characterization is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 62 publications
(119 reference statements)
0
10
0
Order By: Relevance
“…AlHammadi et al [104] have reported that the experimental onsets that are measured by LST(NIR) and HPM methods generally follow a specific pattern, featuring an abrupt increase in the U-AOP values at low temperatures similar to the modeling trend exhibited by the PC-SAFT. They reported that some crude oils demonstrate atypical behavior with the U-AOP curve increasing linearly with a decrease in temperature, as demonstrated in the case with a crude oil from Kuwait (Fig.…”
Section: The Effect Of the Pressure-temperature Changementioning
confidence: 88%
See 3 more Smart Citations
“…AlHammadi et al [104] have reported that the experimental onsets that are measured by LST(NIR) and HPM methods generally follow a specific pattern, featuring an abrupt increase in the U-AOP values at low temperatures similar to the modeling trend exhibited by the PC-SAFT. They reported that some crude oils demonstrate atypical behavior with the U-AOP curve increasing linearly with a decrease in temperature, as demonstrated in the case with a crude oil from Kuwait (Fig.…”
Section: The Effect Of the Pressure-temperature Changementioning
confidence: 88%
“…3 MD/PD -Monodisperse/polydisperse modeling (asphaltene fraction represented by one/several pseudo-component(s)). 4 Liquid phases: Asphaltene-rich and wax-rich phases and bulk crude oil phase searchers [35,[54][55][56][57][60][61][62]104,105]. This method discriminates the stock tank oil (STO) components into four distinct groups including saturates, aromatics, resins, and asphaltenes according to SARA analysis results.…”
Section: The Sara-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SAFT equation of state was proposed by Chapman et al , based on Wertheim’s theory. Its ability to accurately predict phase splitting in systems with large variations of size and shape made it one of the most widely used equations of state. Tremendous success has been shown , in modeling phase behavior of systems of large size differences such as polymers and asphaltene using the SAFT equation of state and its variations (e.g., PC-SAFT). These include systems of complex interaction mixtures of associating and nonassociating components. Examples are the work of Aghaie et al and Kondori et al where they used the PC-SAFT equation of state to model CO 2 solubility in ionic liquids and to evaluate gas hydrates .…”
Section: Introductionmentioning
confidence: 99%